Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Alat-Alat Kesehatan pada PT Inti Medicom Retailindo - Sutama Wisnu Dyatmika; Kresna Agustinengseh (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Researchers conducted research to find out the influence of free variables product quality and price to the variable bound (buying decision) Medical Devices In PT.Inti Medicom Retailindo.Researchers use quantitative data with questionnaires as a means of collecting data used.The method used by researchers is non probability sampling method with purpose sampling technique.With a sample of 100 people have criteria has been made purchases twice or more in PT.Medicom Retailindo core that will be processed using SPSS version 20 program.The results of this study show if there is an influence of significance of the free variable of product quality and price on medical devices in PT.Inti Medicom Retailindo.Based on the results of the t-count test of the three free variables, product quality variables have a value of 6,534 > ttabel > 1,985, the price has a thitung number of > ttabel of 2,032 > 1,985.While looking at the figures based on the results of the F test that the value of Fhitung > Ftabel = 94,722 > 3,089 this means that variable product quality and price simultaneously affect the purchase decision